Age-Based Normative Measurements of the Pediatric Pelvis. Issue 7 (July 2017) - Oetgen, Matthew E.; Andelman, Steven; Martin, Benjamin D.
Abstract : Objectives: Pediatric pelvic trauma is associated with high rates of morbidity and mortality. Current classifications do not take into account age-dependent quantitative differences of the pediatric pelvis making accurate diagnosis of pathologic diastasis of the pubic symphysis, sacroiliac (SI) joints, and triradiate cartilage difficult. The purpose of this study was to establish age-based normative values for the width of the pubic symphysis, SI joints, and the triradiate cartilage of the pediatric pelvis. Methods: All computed tomographic (CT) scans of the abdomen and pelvis from patients between the ages 2 and 16 years over a 3-year period at a single institution were evaluated. Patients were excluded if the CT was performed as part of a trauma evaluation or for a history of neuromuscular disease or spinopelvic instrumentation. A total of 821 CT were included. The width of pubic symphysis, right and left SI joints, and each limb of the triradiate cartilages was measured using the PACS digital measurement tool. Left and right measurements of the SI joints and triradiate cartilage were combined and reported together. Results: From age 2 to 16 years, the average widths of the SI joint and pubic symphysis decreased from 3.11 to 1.80 mm and 5.55 to 3.69 mm, respectively. The average widths of the 3 limbs of the triradiate cartilage also slightly decreased from age 2 until closure: ilioischial, iliopubic, and ischiopubic cartilages decreasing from 3.72 to 2.74 mm, 4.42 to 3.52 mm, and 3.08 to 2.97 mm, respectively. Conclusions: This study demonstrates an age-dependent decrease in width of the pubic symphysis and left and right SI joints. By contrast, the widths of the triradiate cartilage remain relatively stable until closure. We believe that these age-based normative values will aid in future diagnosis of pathologic diastasis of these areas of the pediatric pelvis. Abstract : Supplemental Digital Content is Available in the Text.